1979
DOI: 10.2307/1129431
|View full text |Cite
|
Sign up to set email alerts
|

Configuration and Position Encoding in Children

Abstract: 2 experiments were carried out to clarify the process by which children encode briefly presented spatial positions. The task in both experiments was judging whether a test dot occupied the same position on a card as any 1 of a number of dots which had been presented tachistoscopically. Subjects were first, third, and fifth graders. In the first experiment, performance improved with grade level for stimulus arrays composed of more than 1 dot. The finding contrasts with an earlier report of only minimal developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…2) Mason and Katz (1976) found that good and poor readers among 6th-grade children differed in their ability to identify the relative spatial position of letters. Farkas and Smothergill (1979) also found that performance on a position encoding task improved with grade level in children in 1 st , 3 rd and 5 th grade. 3) It was found that children's reading ability was associated with orientation errors in letter recognition such as confusing d and b, or p and q. stressing the role of visualorthographic skill in reading (e.g., Davidson, 1934Davidson, ,1935Cairns, & Setward, 1970;Terepocki, Kruk, & Willows, 2002).…”
Section: Introductionmentioning
confidence: 78%
“…2) Mason and Katz (1976) found that good and poor readers among 6th-grade children differed in their ability to identify the relative spatial position of letters. Farkas and Smothergill (1979) also found that performance on a position encoding task improved with grade level in children in 1 st , 3 rd and 5 th grade. 3) It was found that children's reading ability was associated with orientation errors in letter recognition such as confusing d and b, or p and q. stressing the role of visualorthographic skill in reading (e.g., Davidson, 1934Davidson, ,1935Cairns, & Setward, 1970;Terepocki, Kruk, & Willows, 2002).…”
Section: Introductionmentioning
confidence: 78%
“…Farkas and Smothergill (1979) also concluded that since the accuracy with which a probe dot could be recognized as belong'ing to a prev'iously presented five-dot pattern increased as pattern goodness increased, patterns were coded as hol'istjc entities. If positions were encoded independently, then pattern goodness (a property of the entire pattern and not of constituent positions ) should not affect recognition accuracy.…”
Section: Resultsmentioning
confidence: 99%